Reciprocal Mobilities in Colonial Encounters in Eighteenth-Century Luzon - Dizon, Mark (Archīum Ateneo, 2022)
The article sheds new light on colonial encounters in eighteenth-century Luzon by viewing them through the lens of mobility. Historical actors—both Spaniards and indigenes—created and sustained ties with each other through reciprocal visits punctuated by feasts. Encounters were not singular events but rather pertained to a series of multiple mobilities and multisited celebrations. The very act of travelling transformed the visitors’ identities, which became ever more entangled with their hosts’. In the colonial context, encounters did not involve a simple unilateral or unidirectional penetration and conquest of the island's interior on the part of Spanish missionaries and officials. They were embedded in a combination of Spanish and indigenous practices of reciprocal mobilities.